Postservice Recovery Customer Satisfaction in Indian Retail Banking: Scale Development and Validation. Issue 4 (1st October 2016) - Mandal, Pratap Chandra; Bhattacharya, Sujoy
ABSTRACT: The construct of postservice customer satisfaction with respect to Indian retail banking has been studied. Furthermore, the development and validation of the postservice recovery customer satisfaction scale in Indian retail banking is detailed. The scale development process was carried out over three stages (item generation, scale purification, scale validation) and comprised of conducting depth interviews and focus groups for item generation and three separate phases of data collection, involving a total of 851 individual respondents. The data provide evidence for face, content, discriminant and convergent validity, dimensionality, reliability, and generalizability of the customer satisfaction scale in Indian retail banking.